Review of FDI Policies in India and China: Analysis and Interpretation - Chitranka K (International Journal of Engineering and Management Research, 2022)
<p class="zw-paragraph" data-linerule="auto" data-line-height="1.5" data-textformat=""ff":"Liberation Serif,Times New Roman","size":12" data-margin-bottom="8.0pt" data-doc-id="5421454000000038006" data-doc-type="writer">Foreign Direct Investment (FDI) is a wide word that encompasses any long-term investment made in the host nation by a non-resident enterprise. Typically, the investment is undertaken over a lengthy period of time with the purpose of maximizing the host nation's advantages, such as superior (and cheaper) resources, consumer market access, or direct access to the host country. All talent improves efficiency. This long-term cooperation will benefit both the investor and the host nation. If the investor makes the same investment in his own nation, he will obtain a larger return, but the host country will profit by boosting the transfer of knowledge or technology to its workforce, putting more pressure on his local business to compete. Foreign firm that can develop the sector as a whole or serve as an example for other companies thinking about investing in the host nation.